Life cycle assessment to identify environmental improvements in an aerobic waste water treatment plant (2023)
Currently, reduce the environmental impacts generated by industries is vital; that is the reason why many companies are changing their processes to biotechnological processes which seem to be more sustainable alternatives. The Life Cycle Analysis (LCA) is an internationally accepted tool that allows environmental assessment of products and processes. In addition, LCA has been used to identify environmental improvement opportunities in different production systems and, that is the reason why it has been selected to be used on this research in order to diagnose the environmental performance of a Waste Water Treatment Plant (WWTP) of a cattle benefit plant. The system studied was a WWTP located in Cúcuta (Colombia), which treats 118.477 kg/day of water from cattle benefit plant. The stages of the WWTP are: screening, grit removal, primary sedimentation tank, homogenizer, grease traps, activated sludge reactor, secondary sedimentation tank, slow down flow filter and drying bed. In this paper the process diagrams and the mass and energy balances were constructed with information provided directly by the cattle benefit plant. The impact analysis was carried out using the software SIMAPRO 7.0 and the following impact categories were evaluated: climate change, eutrophication, photochemical oxidation, depletion of the ozone layer, acidification and biotic exhaustion. It was found that the environmental impacts of the WWTP of the cattle benefit plant are generated mainly due to the high electricity consumption in screening, homogenizer, and slurry reactor. Eutrophication was also observed due to the enrichment caused by the increase of the amounts of nutrients, which affected decomposition of excess of organic matter in the water so it could not be a complete mineralization of the nutrients it possesses. All the calculations were carried out using the Ecoinvent data bases. Favourable indicators were observed comparing the environmental profiles of the biological WWTP under study with the environmental indicators of a physicochemical WWTP of cattle benefit plant located in Bucaramanga (Colombia). The potential environmental impacts were lower in all the impact categories evaluated. © 2016, AIDIC Servizi S.r.l.